POLA PENYEDIAAN DAN POTENSI HIJAUAN DI KAWASAN INDUSTRI KECAMATAN CITEUREUP KABUPATEN BOGOR - Setiana, M.A; Ikmahwati, S; Prihantoro I (Udayana University, 2016)
The aims of this research was to identify and analyze potential forage in different area of Citeureup subdistrict, Bogor regency. This research done by identifying the six villages located in densely populated area industry and one village still have relatively much forage. Analysis of botanical composition is selected to identify the forage variety, capacity analysis, measurement of soil pH and analyze the lead (Pb) content in forage, water and soil. The results is area that has great development in industry affect proportion and forage variety and has forage potential less. The pattern of the provision of forage for a village that has great development in industry, tending to obtained from outside the village (cut and carry). This is because of the metal lead high on the ground in the village so that the growth of forage disturbed and the quality of forage doubtful. Keywords: Lead (Pb), industry, forage, and carrying capacity.